KAJIAN KARAKTERISTIK KEMANDIRIAN DESA SUNGAI RENGAS KECAMATAN SUNGAI KAKAP - Kamaria, Siti; Hernovianty, Firsta Rekayasa; Pratiwi, Nana Novita (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2023)
Sungai Rengas Village has the status of an independent village with a Developing Village Index (IDM) value of 0.905. Sungai Rengas Village has the potential to be developed, but there are also problems that will become challenges in the future in maintaining the village's independent status, for this reason it is necessary to conduct a characteristic study to see the potential and problems that exist in Sungai Rengas Village. Thus, the purpose of this research is to identify the characteristics of the independence of Sungai Rengas Village with a qualitative approach, and descriptive analysis techniques. The results of the study show that Sungai Rengas Village has potential and problems from several aspects studied, namely geographical conditions with a fairly large area, but flooding still occurs in several village areas, the condition of the access road is good even though there are still access roads to other villages in damaged condition, overcrowding the population is relatively low, there are social and cultural activities, infrastructure is adequate although there are still problems in quantity and quality, economic productivity is supported by agriculture and plantations, but there are still constraints from supporting facilities and infrastructure, institutions have been formed but are still not active. Keywords: village, characteristics, independence